2021
DOI: 10.36401/jipo-21-10
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of the Gut Microbiome in the Cancer Response to Immune Checkpoint Inhibitors: A Narrative Review

Abstract: The discovery of immune checkpoint inhibitors (ICIs) has revolutionized the care of cancer patients. However, the response to ICI therapy exhibits substantial interindividual variability. Efforts have been directed to identify biomarkers that predict the clinical response to ICIs. In recent years, the gut microbiome has emerged as a critical player that influences the efficacy of immunotherapy. An increasing number of studies have suggested that the baseline composition of a patient's gut microbiota and its dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 109 publications
(175 reference statements)
0
3
0
Order By: Relevance
“… 79 Moreover, different reviews provided insight into the potential of novel cancer therapies such as immunotherapy, CAR-T cells, and CDk-7 inhibitors in the treatment of oncological diseases. 80 83 As for hematological diseases, one retrospective multicenter observational study confirmed that Eltrombopag, a medication used to treat thrombocytopenia and severe aplastic anemia may be used as second- or third-line therapy in pediatric patients with chronic and refractory idiopathic thrombocytopenia. 84 Another phase 2 trial confirmed that, a new hemoglobin oxygen-affinity modulator, improves Hemoglobin levels and markers of hemolysis in pediatric patients with sickle cell disease and has the potential to mitigate sickle cell disease-related complications in patients aged ⩾4 years.…”
Section: Resultsmentioning
confidence: 99%
“… 79 Moreover, different reviews provided insight into the potential of novel cancer therapies such as immunotherapy, CAR-T cells, and CDk-7 inhibitors in the treatment of oncological diseases. 80 83 As for hematological diseases, one retrospective multicenter observational study confirmed that Eltrombopag, a medication used to treat thrombocytopenia and severe aplastic anemia may be used as second- or third-line therapy in pediatric patients with chronic and refractory idiopathic thrombocytopenia. 84 Another phase 2 trial confirmed that, a new hemoglobin oxygen-affinity modulator, improves Hemoglobin levels and markers of hemolysis in pediatric patients with sickle cell disease and has the potential to mitigate sickle cell disease-related complications in patients aged ⩾4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Clostridium and Firmicutes have been linked to enhanced immunoregulatory responses, related to modification of the T-cell response which may directly enhance the effects of immunotherapy (Shim et al, 2023). Ruminococcus , on the other hand, has been associated with both pro– and anti-inflammatory effects, particularly related to increases in CD4+ and CD8+ T cells, potentially influencing the outcomes of immune checkpoint therapies (Araji et al, 2022). Additional recurrence-associated taxa identified in this study include Lawsonia, Bariatricus, and Blautia, the latter of which was also associated with ICB treatment outcomes in our previous pilot research (Peters et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One potential reason for the varying efficacies of immune checkpoint blockade is the gut microbiome ( 8 10 ). Microbiome and microbiota are often used interchangeably, but the difference between the terms is that microbiome refers to “the collective genomes of microorganisms in a particular environment”, whilst microbiota refers to “the community of microorganisms themselves” ( 11 ).…”
Section: Introductionmentioning
confidence: 99%